HCFC1 variants in the proteolysis domain are associated with X‐linked idiopathic partial epilepsy: Exploring the underlying mechanism - Na He; Bao‐Zhu Guan; Jie Wang; Han‐Kui Liu; Yong Mao; Zhi‐Gang Liu; Fei Yin; Jing Peng; Bo Xiao; Bei‐sha Tang; Dong Zhou; Guang Huang; et al. (Clinical and Translational Medicine, 2023)
Abstract Background HCFC1 encodes transcriptional co‐regulator HCF‐1, which undergoes an unusual proteolytic maturation at a centrally located proteolysis domain. HCFC1 variants were associated with X‐linked cobalamin metabolism disorders and mental retardation‐3. This study aimed to explore the role of HCFC1 variants in common epilepsy and the mechanism underlying phenotype heterogeneity. Methods Whole‐exome sequencing was performed in a cohort of 313 patients with idiopathic partial (focal) epilepsy. Functional studies determined the effects of the variants on the proteolytic maturation of HCF‐1, cell proliferation and MMACHC expression. The role of HCFC1 variants in partial epilepsy was validated in another cohort from multiple centers. Results We identified seven hemizygous HCFC1 variants in 11 cases and confirmed the finding in the validation cohort with additional 13 cases and six more hemizygous variants. All patients showed partial epilepsies with favorable outcome. None of them had cobalamin disorders. Functional studies demonstrated that the variants in the proteolysis domain impaired the maturation by disrupting the cleavage process with loss of inhibition of cell growth but did not affect MMACHC expression that was associated with cobalamin disorder. The degree of functional impairment was correlated with the severity of phenotype. Further analysis demonstrated that variants within the proteolysis domain were associated with common and mild partial epilepsy, whereas those in the kelch domain were associated with cobalamin disorder featured by severe and even fatal epileptic encephalopathy, and those in the basic and acidic domains were associated with mainly intellectual disability. Conclusion HCFC1 is potentially a candidate gene for common partial epilepsy with distinct underlying mechanism of proteolysis dysfunction. The HCF‐1 domains played distinct functional roles and were associated with different clinical phenotypes, suggesting a sub‐molecular effect. The distinct difference between cobalamin disorders and idiopathic partial epilepsy in phenotype and pathogenic mechanism, implied a clinical significance in early diagnosis and management.